DISTANCE LEARNING TOOLS AND THEIR PRINCIPLES APPLICATIONS IN THE STUDY PROCESS MILITARY AND TECHNICAL DISCIPLINES FUTURE OFFERS - Lukin, V.Ye. (Pedagogy of Higher and Secondary Education, 2008)
In the article the method of forming experiment on verification of the pedagogical terms of effective application of facilities of the controlled from distance studies in the process of study of militarytechnical disciplines by the future officers of radio engineering troops is described.